Regional transport networks and competencies: - a case study of transport chains in the furniture industry of Salling - Hansen, Leif Gjelsing (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
The paper is based on a research project with a focus on inter-firm networks in transport chains and their territorial embeddednes. The furniture industry in Salling, in the western part of Denmark, is characterised by a large number of firms concentrated in a small area. The firms represents a regional inter-firm network and a concentration of a specific activity that influences the transport of input (wood) to and output (furniture) from the local furniture industry. The scope of the project has been to: - analyse the geography of transport corridors and composition of transport chains related to the furniture industry - identify the location of compentencies (organisationally and geographically) in the transport chains connecting the value chain of the furniture industry in Salling